Situation Report: Poland, 11 January 1989 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. A Busy End to 1988 / by Anna Swidlicka Walesa and Polish Politics / by Jan de Weydenthal Solidarity "Working Group" Demands Resumption of Solidarity's Statutory Activities / by Anna Swidlicka The Draft Law on Associations / by Anna Swidlicka Defense Budget to Be Reduced / by Roman Stefanowski Veteran Dissident Aniela Steinsbergowa Dies / by Roman Stefanowski Miscellaneous Items / by Roman Stefanowski